SİYER YAZICILIĞININ PROBLEMLERİNE BİR ÖRNEK-Beni Kaynuka Savaşının Sebebi- - Mehmet Azimli (İslami İlimler Dergisi)
The reason of the war against the jewish tribe banu qaynuqa is assessed in this paper. There are two traditional narrations concerning the reason of the war. One of them narrates that jewish tried to put off a muslim woman’s scarf and that was the reason for the war. The paper is formed on this narration with an evaluation of its rawis and sanad and especially historical value. It is clear that this narration was essantially about a event occured in Ficar wars and lately adapted to the the war of banu qaynuqa. And after, this narration become a part of the evidences and records and took part in the Islamic cronicles.